2005
DOI: 10.1167/iovs.05-0362
|View full text |Cite
|
Sign up to set email alerts
|

Brain-Derived Neurotrophic Factor Gene Delivery to Müller Glia Preserves Structure and Function of Light-Damaged Photoreceptors

Abstract: These data provide proof of the concept that BDNF gene transfer into Müller cells is an effective strategy for preserving structure and function of photoreceptors in retinal degeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
1
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(46 citation statements)
references
References 58 publications
1
42
1
1
Order By: Relevance
“…Meanwhile, Di Polo et al 121 reported a persistent expression of Ad-mediated BDNF by transduced Muller cells which had promoted survival of axotomized RGCs, but not for long-term. Next, Gauthier et al 122 showed that BDNF gene transfer by AAV to Muller cells had served as a promising strategy to protect photoreceptors from light-induced retinal degeneration. Another study that explored the possibility of using recombinant AAV serotype 2 (AAV2) to deliver BDNF, revealed that this virus was able to provide efficient transduction of ganglion cells rather than Muller cells.…”
Section: Viral Mediated Bdnf Deliverymentioning
confidence: 99%
“…Meanwhile, Di Polo et al 121 reported a persistent expression of Ad-mediated BDNF by transduced Muller cells which had promoted survival of axotomized RGCs, but not for long-term. Next, Gauthier et al 122 showed that BDNF gene transfer by AAV to Muller cells had served as a promising strategy to protect photoreceptors from light-induced retinal degeneration. Another study that explored the possibility of using recombinant AAV serotype 2 (AAV2) to deliver BDNF, revealed that this virus was able to provide efficient transduction of ganglion cells rather than Muller cells.…”
Section: Viral Mediated Bdnf Deliverymentioning
confidence: 99%
“…Lentiviral vectors were used because of their transgene capacity, rapid onset of expression, and robust and sustained gene expression profile (37). Intravitreal injection of a lentivirus expressing the GFP gene (lnv-GFP) prior to OIR showed a widespread localization and distribution of GFP fluorescence throughout the retinal layers (supplemental Fig.…”
Section: Regulation Of Ctgf/ccn2 Gene Expression In the Retinal Vascumentioning
confidence: 99%
“…Studies performed in normal and retinal degenerate rat models demonstrate that BDNF has a neuroprotective role (Chaum, 2003;Gauthier et al, 2005;Ikeda et al, 2003;Keegan et al, 2003;Lawrence et al, 2004;Nakazawa et al, 2002;Paskowitz et al, 2004). Therefore, the present investigation evaluates the possible role of BDNF in promoting the functional efficacy of the retinal neuroblastic sheets transplanted into the subretinal space of retinal degenerative rats.…”
Section: Introductionmentioning
confidence: 99%